Penerapan Fungsi Pengawasan Untuk Meningkatkan Kinerja SDM di Filantropi Islam - Puspa Aulia Pangestika; Ade Yuliar; Muhammad Saidun (Badan Koordinasi Kegiatan Kesejahteraan Sosial, 2024)
The supervisory function in philanthropic institutions is needed to increase public trust in the institution. In this case, supervisory management of human resources in Islamic philanthropy is needed as a prevention of irregularities in zakat, infaq, shadaqoh (ZIS) funds such as misuse of funds, corruption, and nepotism In addition, it serves to improve the performance of amil Islamic philanthropy. The purpose of this research is to find out how the amil supervision process in field activities (outdoor) at Solo Peduli Foundation. The results of this study indicate that the process of supervising amil field activities (outdoor) is carried out directly and indirectly. Directly using two methods, namely the scriptsheet method and periodic evaluation meetings. Indirect supervision uses the SIM (Information System) Application, which makes it easier to supervise employees when working outside